PERILAKU SOSIAL DALAM CERITA BUNGA ALLUQ DAN DOLITAU (Social Behavior in “Bunga Alluq dan Dolitau” Folklore) - Murmahyati Mahmud (Balai Bahasa Sulawesi Selatan, 2014)
The research is done to uncover social behavior of characters in Bunga Alluq and Dolitau folklore. Method used is descriptive by sociological approach. Result of analysis shows that social behavior of characters in the story is commonly found in society. The husband’s character of Bunga Alluq is describe as unresponsible husband. While, Bunga Alluq is described as loyal wife. The character owned by Bunga Alluq husband is not recommendable. The behavior described in the story is social critic of the author in order to be example which is not worth to follow in household life.